Hysterectomy for dysfunctional uterine bleeding in women with previous tubal sterilization - Ranganna, Hethyshi; Shivlingiaha, Nirmala (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Post tubal ligation syndrome has been a topic of debate with various studies concluding contradictory results. Hysterectomy can be considered as a continuum of the post ligation syndrome due to prolonged menstrual complaints. The present study was done to evaluate any association of tubal sterilization with hysterectomy in patients presenting with dysfunctional uterine bleeding. Methods: The study was conducted in a medical college hospital. Analysis of case files of patients who had undergone hysterectomy for dysfunctional uterine bleeding between May 2012 - May 2013 was done to note the history of prior tubal sterilization. Patients with fibroid uterus, adenomyosis, hypothyroidism, endometrial polyp, cervical polyp and those who had a hysterectomy for nonmenstrual complaints were excluded. Results: 322 patients were hysterectomised during the study period. Among them only 36 patients had a hysterectomy purely for dysfunctional uterine bleeding. Out of the 36 patients, 33 patients (90.9%) had undergone prior tubal sterilization. Hysterectomy was done after a mean duration of 19.31 ± 5.35 years after tubal sterilization. The mean age at onset of menorrhagia was at 42.05 ± 4.71 years. Conclusions: Tubal sterilization is a risk factor for future hysterectomy in patients with dysfunctional uterine bleeding.